EFFECT OF RAW MATERIAL PROPORTIONS ON THE QUALITY OF COMPOST FROM CLOVE LEAF LITTER AND CATTLE MANURE - Kartini, Ni Luh; Bimantara, Putu Oki; Vanessa; Hutagalung, Trianita Br.; Grace, Querida Maria; Rucika, I Wayan Alit; Pardosi, Ivana Cein; Sitanggang, Manumpak Pardingotan; Anggarini, Ni Wayan Sri; Maulidhya, Rachel; Simbolon, Randa; Manihuruk, Yesika (Universitas Veteran Bangun Nusantara, 2026)
Agricultural and livestock wastes are widely available in clove-producing areas but remain underutilized as organic fertilizer inputs. This study aimed to evaluate the quality of compost produced from clove leaf litter, cattle manure, and agricultural residues based on physical and chemical characteristics. The experiment was arranged using a randomized block design with nine treatment combinations and three replications. Compost quality parameters analyzed included organic carbon content, total nitrogen, and C/N ratio. Data were subjected to analysis of variance followed by Duncan’s Multiple Range Test at a 5% significance level. The results showed that variations in raw material proportions significantly affected all measured compost quality parameters. Compost formulations with balanced proportions of cattle manure, clove leaves, and agricultural residues resulted in lower C/N ratios, indicating improved compost maturity and stability compared to unbalanced material combinations. These findings demonstrate that locally available agricultural and livestock wastes can be effectively processed into high-quality compost, providing a practical approach to organic waste utilization and supporting environmentally friendly agricultural practices in clove-producing regions. Keywords: agricultural residues, cattle manure, clove leaf litter, compost quality, organic fertilizer